MINAT SISWA SDN 3 RUMBUK KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR TERHADAP CABANG OLAHRAGA TENIS MEJA - Muhammad Rosyihan Anwar; Johan Irmansyah; Aminullah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Interest is the driving force that encourages individuals to engage in activities they enjoy and is stable, related to the rights they are interested in. This study aims to determine the interest of students at SDN 3 RUMBUK, Sakra District, East Lombok Regency, in table tennis sports. This descriptive research was conducted in April 2024 with a sample of 42 students selected through random sampling. Data were collected using questionnaires and analyzed quantitatively using percentage formulas. The results show that for the attention indicator, 48% of students were categorized as very good, 51% as good, and 1% as moderate; for the liking and interest indicator, 48% were very good, 51% good, and 1% moderate; for the activity indicator, 48% were very good, 51% good, and 1% moderate; for the teacher and coach role indicator, 49% were very good, and 51% were good; for the facility indicator, 48% were very good, and 52% were good; for the family indicator, 35% were very good, and 65% were good; for the environment indicator, 41% were very good, and 59% were good. The conclusion of this study is that the interest of students in table tennis sports at SDN 3 RUMBUK falls into the good category with the highest percentage.